Expert Approach to Solving Tasks of Identifying Areas on Credit Funds Spending in the Course of Forensic Economic Examination - M. M. Vinogradova (Теория и практика судебной экспертизы, 2025)
The article considers the theoretical basis for class division of forensic economic examinations into types and kinds by various expert institutions.The type classification of forensic financial and economic examinations is proposed depending on the financial relations between business activity subjects which are to be investigated.The subject of forensic financial and credit examination is defined as financial relations between a creditor and a borrower. The tasks of this type of forensic economic examination are analyzed. Expert approaches to solving one of the frequent tasks of forensic financial and credit examination are analyzed related to establishing the areas of credit funds spending.Basic normative documents regulating the activity of credit organizations and their rules of accounting are listed. A number of professional terms related to finance and credit activities as well as the structure of the client’s bank account number are analyzed as well.The logic of an economist’s actions is shown using an example from expert practice when addressing typical questions on obtaining and spending a bank loan.Interpretations of key professional terms are given for those who do not possess special knowledge in finance and credit to understand the text of an economic expert’s conclusion.